2022
DOI: 10.1007/s10549-022-06683-4
|View full text |Cite
|
Sign up to set email alerts
|

Clever-1 positive macrophages in breast cancer

Abstract: Purpose Common Lymphatic Endothelial and Vascular Endothelial Receptor 1 (Clever-1) is expressed by a subset of immunosuppressive macrophages and targeting the receptor with therapeutic antibodies has been shown to activate T-cell-mediated anti-cancer immunity. The aim of this research was to study Clever-1 expression in breast cancer. Specifically, how Clever-1 + macrophages correlate with clinicopathologic factors, Tumor Infiltrating Lymphocytes (TILs) and prognosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
4
1
Order By: Relevance
“…Intratumoral STAB1+ macrophage infiltration correlated with improved patient outcome and higher CD8+ T cell infiltration. However, no significant effects on patient outcome or immune cell infiltrate were correlated with STAB1+ macrophages localized to the peritumoral stroma 136 . This study contradicts current literature regarding reported STAB1+ macrophage functionality; thus, more studies are needed to understand this macrophage subset.…”
Section: Emerging Macrophage Subsets In the Tumor Microenvironmentcontrasting
confidence: 78%
See 2 more Smart Citations
“…Intratumoral STAB1+ macrophage infiltration correlated with improved patient outcome and higher CD8+ T cell infiltration. However, no significant effects on patient outcome or immune cell infiltrate were correlated with STAB1+ macrophages localized to the peritumoral stroma 136 . This study contradicts current literature regarding reported STAB1+ macrophage functionality; thus, more studies are needed to understand this macrophage subset.…”
Section: Emerging Macrophage Subsets In the Tumor Microenvironmentcontrasting
confidence: 78%
“…50,135 STAB1+ macrophages have additionally been found in samples from human breast cancer patients, and the effects of STAB+ expression on patient outcome were stratified based on localization within the tumor. 136 Intratumoral STAB1+ macrophage infiltration correlated with improved patient outcome and higher CD8+ T cell infiltration. However, no significant effects on patient outcome or immune cell infiltrate were correlated with STAB1+ macrophages localized to the peritumoral stroma.…”
Section: Publicationmentioning
confidence: 87%
See 1 more Smart Citation
“…These preclinical results led to a phase 1 trial to determine the safety and preliminary effectiveness of FP-1305, a humanized anti-Clever-1 antibody administered to heavily pretreated patients with metastatic solid tumors (269). Encouraging results of this trial indicated a proinflammatory switch of monocytes, enhanced capability of macrophages to cross-present scavenged antigens, and activation of T cells (270). TAMs also express PD-1, which inhibits phagocytosis and tumor immunity, impairing the PD-1/ PD-L1 axis in macrophages.…”
Section: Other Checkpoint Signaling Pathwaysmentioning
confidence: 90%
“…These preclinical results led to a phase 1 trial to determine the safety and preliminary effectiveness of FP-1305, a humanized anti-Clever-1 antibody administered to heavily pretreated patients with metastatic solid tumors ( 269 ). Encouraging results of this trial indicated a proinflammatory switch of monocytes, enhanced capability of macrophages to cross-present scavenged antigens, and activation of T cells ( 270 ). TAMs also express PD-1, which inhibits phagocytosis and tumor immunity, impairing the PD-1/PD-L1 axis in macrophages.…”
Section: Tam-targeted Therapiesmentioning
confidence: 99%